The Integrity of State Civil Apparatus in the Regional Election Process (Case Study of Bone District) - Andika Wahyu Gani; Muhammad Luthfi Siraj; Dyan Paramitha Darmayanti; Andra Ramadhan (Pinisi Journal of Social Science, 2023)
This research aims to determine the extent to which the Integrity of the State Civil Apparatus in the election of the Regional Head of Bone Regency. The research method used is a qualitative method with a type of case study whose research focus lies on contemporary (current) phenomena in a real life context. Determination of informants purposively based on those who are directly involved with the problem. Data collection techniques using observation, interviews and documentation. The results of the study show that the integrity of the state civil apparatus in Bone Regency is considered a poor indicator, namely the indicator of honesty, while there are two indicators that have been fulfilled, namely consistency and courage. Good. Based on this, the State Civil Apparatus in the Election of Regional Heads of Bone Regency is considered to have fairly good integrity, although there are still a small number of those who violate the ASN code of ethics who are not neutral in the implementation of the regional elections